PEMAKNAAN KONTEN MARRIAGE IS SCARY DALAM KONSEP DIRI REMAJA - Calista Ladyva Aurellia; Noor Afy Shovmayanti; Kurniawan Dani (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2026)
The Marriage is Scary phenomenon, which has been widely discussed on social media, shows that Generation Z, especially women, have a fear of marriage. This study aims to find out how female students understand Marriage is Scary content on social media and how it relates to identity formation. This study uses a qualitative method with a phenomenological approach. Data were collected through in-depth interviews using Google Forms with ten active female students from who had seen Marriage is Scary content. Data analysis was conducted in three steps, namely open coding, axial coding, and selective coding. The results showed that social media served as the initial cause of fear of marriage by displaying various problems in households, failures in relationships, and gender role inequality. However, the female students did not simply accept these stories without thinking. Some respondents saw them as a reflection that encouraged them to strengthen their identity, be careful in forming relationships, and prepare themselves mentally, socially, and economically before getting married. This study shows that the Marriage is Scary phenomenon illustrates how Generation Z negotiates meaning and shapes their identity in the world of digital communication.